Analisis Pengelolaan Limbah Praktikum Biologi di Madrasah Aliyah X, Tangerang Selatan - Nasywa Alfia Alifatunnisa; Syabrina Syahla Zulfaa Nazhifah; Yesi Noviliani; Asfi Royani; Evi Muliyah (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
A biology laboratory is a room for experiments and research to understand biological concepts and each experiment. Science laboratory standardization is regulated by Minister of National Education Regulation no. 24 of 2007. This research aims to increase awareness about the importance of effective and efficient waste management. The research was conducted at Madrasah Aliyah X, South Tangerang, for the 2024/2025 academic year. The research methods used in collecting data were interviews, observation, and documentation, which were then presented descriptively. The results of interviews with laboratory assistants and biology teachers were described qualitatively, observational data were described quantitatively in percentages, and documentation was used as research-supporting data. Waste management at Madrasah Aliyah X, South Tangerang, is included in the excellent category. Waste management needs to be developed by collaborating with external parties so that waste management is optimal and there is no accumulation of waste.